Incorporating Bioinformatics into Biological Science in Nepal: Prospects and Challenges - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2013)
The huge amount of data created by proteomics and genomics studies worldwide has caused bioinformatics to gain prominence and importance for urgency to process and analyze those data. However, its multidisciplinary nature has created a challenge to meet the unique demand for specialist trained in both biology and computing. Several countries, in response to this challenge, have developed a number of manpower training programs. This review presents a description of the meaning, scope, history and development of bioinformatics with focus on prospects and challenges facing bioinformatics education worldwide. The paper also provides an overview of attempts at the introduction of bioinformatics; describes the existing bioinformatics scenario and suggests strategies for effective bioinformatics education for the sustainable growth and development in Nepal. Academic Voices, Vol. 2, No. 1, 2012, Pages 78-85 DOI: http://dx.doi.org/10.3126/av.v2i1.8294